The Effect of Temperature and Storage Time on the Quality of Frozen Food Nuggets - Lastri Wiyani; Gusnawati; Muhammad Fauzan; Nur Annisa (Fakultas Teknologi Industri - Universitas Muslim Indonesia, 2025)
This study aims to determine the effect of storage temperature on the quality of nuggets (frozen food) and the effect of storage time on their quality.The test results showed that the Total Plate Count at room temperature (28ºC-30ºC) on day 1 did not meet the standard. Similarly, at refrigerator temperature (10ºC), the values on days 12 and 16 did not meet the standard. Meanwhile, at freezer temperature (-16ºC), all samples met the standard of <105 cfu/g. For the Yeast and Mold test, the results did not meet the standard at room temperature (28ºC-30ºC) on day 1 and at refrigerator temperature (10ºC) on days 12 and 16. However, at freezer temperature, the nugget samples met the standard requirement of a maximum of 1 × 10⁴ cfu/g.The E. coli test results for all storage conditions (room temperature, refrigerator, and freezer) met the requirement of <3 cfu/g. For the Coliform test, the sample stored at room temperature on day 1 did not meet the requirement, whereas samples stored at refrigerator and freezer temperatures met the standard of 10 cfu/g. In the Proximate Analysis, nuggets stored at room temperature had a moisture content of 51.66%, protein content of 9.62%, and fat content of 10.05%. Meanwhile, those stored at freezer temperature had a moisture content of 61.48%, protein content of 10.23%, and fat content of 10.36%. However, some proximate components, such as moisture and fat content, increased during storage.